Heat-absorbing sexual coloration co-adapts with increased heat tolerance in dragonflies - Leith, Noah T.; Moore, Michael P. (Frontiers in Ethology, 2024)
Producing and maintaining sexually selected ornaments often hinders survival. Because viability-related traits dictate the survival costs conferred by sexual ornaments, the evolution of viability-related traits can limit and/or compensate for ornament evolution. Here, we examine how the ornamental coloration of male dragonflies co-adapts with thermal physiology-a key suite of viability-related traits that influences nearly all reproductive and ecological interactions. Males of many dragonfly species produce dark color patches on their wings to attract potential mates and intimidate reproductive rivals. However, dark coloration also subjects male dragonflies to heat stress in warm climates by absorbing excess solar radiation. Our phylogenetic comparative analyses revealed that dragonfly species with dark sexual coloration have also evolved increased critical thermal maxima, which may allow them to compensate for ornament-induced heating. This pattern of correlated evolution was especially strong for species that inhabit tropical climates, where the heating costs of dark coloration are most severe. Given that darkened sexual coloration is taxonomically widespread and consistently elevates body temperatures, the pattern of co-adaptation between sexual ornaments and thermal physiology found here could represent a key process driving eco-physiological divergence in the past and influencing how populations respond to the changing climates of the future.